Validity and reliability of different kinematics methods used for bike fitting - Fonda, B.; Sarabon, N.; Li, F.-X. (Journal of Sports Sciences, 2014)
The most common bike fitting method to set the seat height is based on the knee angle when the pedal is in its lowest position, i.e. bottom dead centre (BDC). However, there is no consensus on what method should be used to measure the knee angle. Therefore, the first aim of this study was to compare three dynamic methods to each other and against a static method. The second aim was to test the intra-session reliability of the knee angle at BDC measured by dynamic methods. Eleven cyclists performed five 3-min cycling trials; three at different seat heights (25°, 30° and 35° knee angle at BDC according to static measure) and two at preferred seat height. Thirteen infrared cameras (3D), a high-speed camera (2D), and an electrogoniometer were used to measure the knee angle during pedalling, when the pedal was at the BDC. Compared to 3D kinematics, all other methods statistically significantly underestimated the knee angle (P = 0.00; ny2 = 0.73). All three dynamic methods have been found to be substantially different compared to the static measure (effect sizes between 0.4 and 0.6). All dynamic methods achieved good intra-session reliability. 2D kinematics is a valid tool for knee angle assessment during bike fitting. However, for higher precision, one should use correction factor by adding 2.2° to the measured value.